1998
DOI: 10.1080/08990229870871
|View full text |Cite
|
Sign up to set email alerts
|

Laminar differences in bicuculline methiodide's effects on cortical neurons in the rat whisker/barrel system

Abstract: Extracellular unit recordings were made at various depths within SmI barrel cortex of immobilized, sedated rats, in the presence and absence of titrated amounts of the GABA(A) receptor antagonist bicuculline methiodide (BMI). Principal and adjacent whiskers were moved singly, or in paired combination in a condition-test paradigm, to assess excitatory and inhibitory receptive field (RF) characteristics. Neurons were classified as regular- or fast-spike units, and divided into three laminar groups: supragranular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…In the present study, it was determined that layer IV neurons fire an average of 2.69 ms after the thalamocortical neurons, whereas responses of infragranular and supragranular neurons occur 0.92 and 1.84 ms later than the layer IV response. These values are comparable with excitatory postsynaptic potential (EPSP) onset times in in vitro (Agmon and Connors 1992), in vivo intracellular studies (Carvell and Simons 1988;Moore and Nelson 1998) and previous extracellular measurements (Kyriazi et al 1998) of the rat barrel cortex. It is known that layer V pyramidal cells receive direct monosynaptic thalamocortical inputs (Agmon and Connors 1992;see White 1989).…”
Section: Laminar-dependent Response Transformations Within the Corticsupporting
confidence: 66%
See 2 more Smart Citations
“…In the present study, it was determined that layer IV neurons fire an average of 2.69 ms after the thalamocortical neurons, whereas responses of infragranular and supragranular neurons occur 0.92 and 1.84 ms later than the layer IV response. These values are comparable with excitatory postsynaptic potential (EPSP) onset times in in vitro (Agmon and Connors 1992), in vivo intracellular studies (Carvell and Simons 1988;Moore and Nelson 1998) and previous extracellular measurements (Kyriazi et al 1998) of the rat barrel cortex. It is known that layer V pyramidal cells receive direct monosynaptic thalamocortical inputs (Agmon and Connors 1992;see White 1989).…”
Section: Laminar-dependent Response Transformations Within the Corticsupporting
confidence: 66%
“…As an adjacent whisker conditioning stimulus, however, it was effective in inhibiting PW responses evoked by punctate whisker deflection. Condition-test ratios of supra-and, to a lesser extent, infragranular neurons were, on average, somewhat larger (indicative of less response suppression) than those of layer IV barrel neurons, although in a previous study using punctate conditioning stimuli (Kyriazi et al 1998), values were equivalent across cortical laminae. We propose that inhibitory receptive field properties observed superficial and deep to the barrel in the present study reflect preprocessing by barrel circuitry, with considerably less, or possibly even no, direct contribution from the inhibitory circuitry of the supra-and infragranular laminae themselves.…”
Section: Laminar-dependent Response Transformations Within the Corticmentioning
confidence: 89%
See 1 more Smart Citation
“…Because putative inhibitory barrel neurons often have multiwhisker receptive fields (Simons and Carvell, 1989;Swadlow, 1989;Welker et al, 1993), type A neurons may also mediate the adjacent-whisker inhibition observed in vivo (Simons, 1995;Goldreich et al, 1999). Types B, D, and E neurons, with a sphere of influence extending to layers II/III, probably mediate the strong disynaptic inhibition observed in supragranular neurons in vivo (Ferster and Lindstrom, 1983;Kyriazi et al, 1998;Brumberg et al, 1999;Zhu and Connors, 1999) or in vitro (Agmon and Connors, 1992). Finally, inhibitory neurons of morphological type E, with axonal trees that extend tangentially at least one barrel width on either or both sides of the column of origin, will generate the short-latency cross-column inhibition that is a prominent feature in supragranular layers of mouse barrel cortex in vivo (Welker et al, 1993).…”
Section: Morphological Types Of Inhibitory Interneurons and Their Funmentioning
confidence: 99%
“…The short latency of the inhibitory response indicates that the inhibitory interneurons eliciting it must be excited directly by the thalamocortical afferents, consistent with anatomical data (White, 1978;Fairén and Valverde, 1979;Freund et al, 1985;Keller and White, 1987), and in turn inhibit other cortical neurons disynaptically. This feedforward inhibition is a highly robust feature that can be engaged by even a single thalamocortical action potential (Swadlow and Gusev, 2000), can influence the spread of thalamocortically evoked excitation, and can shape the cortical representation of the sensory environment (Sillito, 1975;Tsumoto et al, 1979;Sillito et al, 1980;Hicks and Dykes, 1983;Dykes et al, 1984;Kyriazi et al, 1996;Kyriazi et al, 1998).…”
mentioning
confidence: 99%